Rachel Carson : A 4D BOOK - Simons, Lisa M. Bolt, 1969-; Shores, Erika L.; Server, Jessica; Whitman, Charmaine (North Mankato, Minnesota : CAPSTONE PRESS, 2018)
"Rachel Carson wasn't just a scientist. She was an author and a conservationist. Young readers will discover how this biologist helped bring attention to the dangers of pesticides and the need for protecting the environment. Download the Capstone 4D app to access a variety of bonus content."--Provided by publisher.
Includes index.
Bibliography : page 23
Interest age level: Ages 6-9.
Keywords: Carson, Rachel, -- Juvenile literature -- 1907-1964; Biologists -- Juvenile literature -- Biography -- United States; Environmentalists -- Juvenile literature -- Biography -- United States; Science writers -- Juvenile literature -- Biography -- United States